The Evaluation of Free Education Program at North Kayong District in 2016Period - Heru Suherda; Maswardi M. Amin; Fadillah Fadillah (JETL (Journal of Education, Teaching and Learning), 2019)
North Kayong as a new district for regional autonomy, the elected Bupati formed an assessment team which later identified the Education problems in North Kayong, namely the lack of schools and their distribution in each sub-district, and the weak support capacity of the community towards education funding, with the limited budget of the Kayong Utara regional government initiating a free education program with the aim of improving access to Education and Quality of Education. Public policy cannot be released as soon as it has been established, policies must be monitored and one form of the monitoring mechanism is policy evaluation. This study aims to conduct, context evaluation to find out the legal basis, background and objectives of the program, evaluation of input to find out the characteristics of the recipient of the program, providers, and sources of financing, process evaluation to find out the time allocation, mechanism for the process of financing and program implementation, and evaluation product to find out the achievements in this free education program. Evaluation is done with the CIPP evaluation model. The results of the study 1) In the context component known, the legal basis of the implementation of the free education program is the Regent Regulation No. 60A in 2009 and the Kayong Utara District Regulation No. 5 of 2014, in the implementation of free education free education program will be achieved, 2) The Imput component is known that the program targets are school-age children who are domiciled in KKU, and the program implementers are the Education Agency that has management fields for elementary to secondary education, for budgeted funding is always exceeding above 20% of the North Kayong District APBD value with an average of 2010-2016 25.83% of the APBD value, 3) Budgeting is carried out by a mechanism in accordance with the rules of the Ministry of Home Affairs where there is a budget discussion process involving the executive and legislative, on implementation n free education programs, there are two types of activities, namely School Operational Assistance to finance school management and investment funds in the education sector, 4) the results achieved in 2016 are the increase in the number of TK / SD / SD from 101 schools to 206 schools, SMP / MTs from 32 Schools become 44 Schools, and High Schools / Vocational Schools / MAs from 9 Schools to 22 Schools. The increase in the APK value in 2016 for elementary school level to 125.4%, junior high school 96.77%, and high school to 74.08%. The APM value also increased, in 2016 the NER SDN became 99.94%, the NER junior high school became 72.32%, and the NER SMA became 48.96. School dropouts were also very low in 2016 to 0.00 at the elementary school level, 0.04 at the junior high school level, and 0.29 at the senior high school level.